Enhancing production of ergosterol in Pichia pastoris GS115 by over-expression of 3-hydroxy-3-methylglutaryl CoA reductase from Glycyrrhiza uralensis - Ying Liu; Xiaoqing Zhu; Wendong Li; Hao Wen; Ya Gao; Yong Liu; Chunsheng Liu (Elsevier, 2014)
The rate-limiting enzyme in the mevalonic acid (MVA) pathway which can lead to triterpenoid saponin glycyrrhizic acid (GA) is 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR). In order to reveal the effect of copy number variation in the HMGR gene on the MVA pathway, the HMGR gene from Glycyrrhiza uralensis Fisch. (GuHMGR) was cloned and over-expressed in Pichia pastoris GS115. Six recombinant P. pastoris strains containing different copy numbers of the GuHMGR gene were obtained and the content of ergosterol was analyzed by HPLC. The results showed that all the recombinant P. pastoris strains contained more ergosterol than the negative control and the strains with 8 and 44 copies contained significantly more ergosterol than the other strains. However, as the copy number increased, the content of ergosterol showed an increasing-decreasing-increasing pattern. This study provides a rationale for increasing the content of GA through over-expressing the GuHMGR gene in cultivars of G. uralensis.